Thorstein Veblen's Darwinian framework and gene-culture coevolution theory. Issue 4 (3rd July 2016) - Kologlugil, Serhat
Abstract: At the turn of the previous century, Thorstein Veblen used Darwinian evolutionary principles to explain the macro-historical evolution of human societies, as well as the institutional structure of the modern pecuniary culture. Even if Veblen had a strong intuitive grasp of the evolutionary forces operating in society, he was not always clear and explicit in developing his ideas towards a full-fledged, consistent evolutionary social theory. This paper argues that a relatively recent theoretical approach, gene-culture coevolution theory, has the conceptual apparatus to remedy this problem and thus make Veblen's ideas an important part of contemporary evolutionary thinking in social theory.